On the dynamics of music virality and its relation with mainstream success - Oliveira, Gabriel P.; da Silva, Ana Paula Couto; Moro, Mirella M. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2026.249422, 2026)
Music going viral is not new, but the Web and social platforms have amplified its global reach. While related, virality and commercial success remain distinct. This work analyzes music virality and its relation to mainstream success from a data science perspective through three steps: characterization, causality analysis, and temporal modeling. Results show that artist-related and temporal features best distinguish both phenomena, which can sometimes predict each other. Furthermore, epidemiological models capture viral dynamics more accurately than long-term success. Overall, this work reinforces the differences and symbiotic links between virality and success, contributing to computing, musicology, and the music industry.